1945
DOI: 10.3382/ps.0240252
|View full text |Cite
|
Sign up to set email alerts
|

Distillers’ Dried Solubles in Chick Rations Containing Corn and Vegetable Protein Supplements ,

Abstract: A DESCRIPTION of distillery byproducts, arid a review of the literature concerning the utilization of these by-products in poultry rations, has been given by Synold et al. (1943). Distillers' dried solubles has been reported to be a good source of riboflavin and other vitamins of the B complex (Bauernfeind et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1946
1946
1958
1958

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Recent work by Berry et al (1943) and Marvel et al (1945aMarvel et al ( ), (1945bMarvel et al ( ), (1945c indicates that soybean oil meal is adequate in protein quality, but deficient in some of the vitamins supplied by animal products. Bird and Groschke (1942) reported that the efficiency of feed utilization was greater when combinations of soybean oil meal, corn gluten meal, and some animal protein were fed, than when corn gluten meal was omitted.…”
Section: Departments Of Animal Husbandry and Agricultural Biochemistrmentioning
confidence: 96%
“…Recent work by Berry et al (1943) and Marvel et al (1945aMarvel et al ( ), (1945bMarvel et al ( ), (1945c indicates that soybean oil meal is adequate in protein quality, but deficient in some of the vitamins supplied by animal products. Bird and Groschke (1942) reported that the efficiency of feed utilization was greater when combinations of soybean oil meal, corn gluten meal, and some animal protein were fed, than when corn gluten meal was omitted.…”
Section: Departments Of Animal Husbandry and Agricultural Biochemistrmentioning
confidence: 96%
“…In much of the experimental work conducted, a 41 percent protein peanut oil meal has been used in diets high in animal protein, relatively low in energy and fed to birds with a relatively slow rate of growth. Marvel et al (1945) concluded that peanut oil meal could replace soybean oil meal when 10 percent of distiller's dried solubles was included in the diet, although the weights of birds were lower than those fed diets containing meat and bone scraps and dried skim milk. As much as 15 percent of peanut oil meal may replace an equal weight of soybean oil meal in diets used by Hammond (1944).…”
mentioning
confidence: 99%